New Permian fauna from tropical Gondwana - Cisneros, Juan C. (2015)
Terrestrial vertebrates are first known to colonize high-latitude regions during the middle Permian (Guadalupian) about 270 million years ago, following the Pennsylvanian Gondwanan continental glaciation. However, despite over 150 years of study in these areas, the biogeographic origins of these rich communities of land-dwelling vertebrates remain obscure. Here we report on a new early Permian continental tetrapod fauna from South America in tropical Western Gondwana that sheds new light on patterns of tetrapod distribution. Northeastern Brazil hosted an extensive lacustrine system inhabited by a unique community of temnospondyl amphibians and reptiles that considerably expand the known temporal and geographic ranges of key subgroups. Our findings demonstrate that tetrapod groups common in later Permian and Triassic temperate communities were already present in tropical Gondwana by the early Permian (Cisuralian). This new fauna constitutes a new biogeographic province with North American affinities and clearly demonstrates that tetrapod dispersal into Gondwana was already underway at the beginning of the Permian.